Combined Effect of Pore Water Overpressure, Far-Field Stresses, and Strength Parameters in Wellbore Stability - Deangeli, Chiara; Marchelli, Maddalena (Frontiers in Earth Science, 2022)
The paper focuses on the analysis of limit mud pressures to avoid failure by considering the mutual interaction of far field stresses, fluid overpressure, and strength parameters of isotropic rock. We coupled the Mohr-Coulomb criterion and the Hoek and Brown criterion with the Kirsch solution to obtain the expression of the mud pressure in the compression and tension zone, during drilling operations. We carried out parametric analyses in two overpressured fields (North Sea basin and Browse basin). We defined an ESP (Effective Stress Path) failure line that depends on the induced state of stress and pore pressure. The strength parameters determine if the limit condition of failure occurs in the tension zone or in the compression zone along this ESP. A uniaxial compressive condition occurs along the ESP that corresponds to the limit of failure when drilling in balance. The conventional analysis of tensile failure in uniaxial condition gives limits that are different from those corresponding to a general state of stress. We proposed two different slopes of the criterion in the tension and compression zone, because of the uncertainties in the estimation of strength parameters. A high frictional component reduces the extent of the tension zone and results in conservative stability analyses. In general, the Hoek and Brown criterion describes better the conditions of rock failure in tension and in compression. We carried out numerical simulation with FLAC to investigate the extent of failure with different mud pressures. The margin of mud weight between the onset of local failure and borehole collapse is very low at high overpressures. The geomechanical analysis of wellbore stability in overpressured basins indicated the need of improving the log correlations for the determination of the strength parameters of the rock.